2009
DOI: 10.1007/s10508-009-9543-1
|View full text |Cite
|
Sign up to set email alerts
|

The DSM Diagnostic Criteria for Hypoactive Sexual Desire Disorder in Women

Abstract: Hypoactive Sexual Desire Disorder (HSDD) is one of two sexual desire disorders in the Diagnostic and Statistical Manual of Mental Disorders (DSM) and is defined by the monosymptomatic criterion "persistently or recurrently deficient (or absent) sexual fantasies and desire for sexual activity" that causes "marked distress or interpersonal difficulty." This article reviews the diagnosis of HSDD in prior and current (DSM-IV-TR) editions of the DSM, critiques the existing criteria, and proposes criteria for consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
193
2
21

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(219 citation statements)
references
References 111 publications
3
193
2
21
Order By: Relevance
“…40 Interestingly, our results also showed that while relationship satisfaction was a predictor of perceived partner-and interpersonal distress, difficulty to communicate about sexual needs was relevant to the prediction of interpersonal distress, but only for desire impairments. Considering the very high prevalence estimates of low desire in women 41 , the conceptual problems to define (low) desire 42 , and the increasing number of studies suggesting that desire discrepancies within couples are the rule rather than the exception (e.g., 43,44 ), it is possible that couples who are able to communicate about their sexual needs are more likely to perceive desire impairments as an incompatibility between partners. Defining the desire impairment on a dyadic level (thereby avoiding labelling one partner as 'dysfunctional') may not lower the distress the partner feels, but it may prevent sexual impairments from causing relational problems.…”
Section: Discussionmentioning
confidence: 99%
“…40 Interestingly, our results also showed that while relationship satisfaction was a predictor of perceived partner-and interpersonal distress, difficulty to communicate about sexual needs was relevant to the prediction of interpersonal distress, but only for desire impairments. Considering the very high prevalence estimates of low desire in women 41 , the conceptual problems to define (low) desire 42 , and the increasing number of studies suggesting that desire discrepancies within couples are the rule rather than the exception (e.g., 43,44 ), it is possible that couples who are able to communicate about their sexual needs are more likely to perceive desire impairments as an incompatibility between partners. Defining the desire impairment on a dyadic level (thereby avoiding labelling one partner as 'dysfunctional') may not lower the distress the partner feels, but it may prevent sexual impairments from causing relational problems.…”
Section: Discussionmentioning
confidence: 99%
“…21 A woman experiencing problems relating to her partner may not feel desire before arousal, and thus be labelled as less functional. However, as has been stated before, where relationship issues are the basis for a woman's sexual problems, treatment of the man's ED might not result in a concomitant recovery of the woman's sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…The current DSM IV TR definition on female sexual arousal disorder (FSAD) is based mainly on physiological criteria but research literature shows consistently low correlation between subjective reports of arousal and objective physiological changes that occur (21,22). The high overlap of different components of desire and arousal in women, the fact that low sexual arousal often coexist with complaints of low libido and treatment research data supporting that transdermal testosterone used for treatment of HSDD improved not only the desire but also arousal are some of the reasons that led authorities to further recommend merging desire and arousal diagnosis into one single entity called Female Sexual Interest and Arousal Disorder (FSIAD) where a certain amount of a total number of criteria are needed to be met in order to fulfill diagnostic criteria, should be adopted in DSM5 (20,23). Although the idea of merging the two disorders together is still mainly based on clinical judgement rather than sufficient empirical evidence, the suggestion has been welcomed by many professionals and is regarded as one of the most important propositions to be considered in DSM 5.…”
Section: Diagnostic Criteria For Substance-induced Sexual Dysfunctionmentioning
confidence: 99%
“…This suggestion may result in one gender neutral category. One proposition made was to apply FSIAD criteria for men as well with removal of criterion A6 (absent or reduced genital and/or non genital physical changes and sensations) as reviewed thoroughly by Brotto (23). However, the extensive literature exploring epidemiology,and treatment of ED reviewed by Segraves has presented considerable data not to subsume ED under the category of male sexual interest and arousal disorder (MSIAD) due to etiological and-or treatment reasons (34).…”
Section: Regarding Male Sexual Disorders (Msd) It Ismentioning
confidence: 99%